A Novel Multi Ring Forwarding Protocol for Avoiding the Void Nodes for Balanced Energy Consumption - Taj, Thasin; Raghu Kumar, KS (International Journal of Computer Sciences and Engineering, 2025)
To take care of the directing void issue in geographic steering, high control overhead and transmission postponement are as a rule taken in remote sensor systems. Roused by the structure made out of edge hubs around which there is no steering void, a proficient bypassing void steering convention in light of virtual directions is proposed in this paper. The fundamental thought of the convention is to change an irregular structure made out of void edges into a general one by mapping edge hubs directions to a virtual circle. By using the virtual circle, the covetous sending can be kept from falling flat, so that there is no directing void in sending process from source to destination and control overhead can be lessened. Besides, the virtual circle is helpful to lessen normal length of steering ways and abatement transmission delay. Reproductions demonstrate the proposed convention has higher conveyance proportion, shorter way length, less control parcel overhead, and vitality utilization.